IMPLEMENTASI PROGRAM ADIWIYATA DI SMAN 1 BANGKO BAGANSIAPI-API KECAMATAN BANGKO KABUPATEN ROKAN HILIR - Rizka Ninda Septian; Isjoni Isjoni; Fakhri Ras (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2022)
This study aims to identify and describe the Adiwiyata school program at SMAN 1 Bangko. Starting from the program planning stage, implementation to the results that have been made together. Data collection techniques using observation, interviews, and documentation. The data analysis used a qualitative descriptive technique. The results of the research where the Adiwiyata program at SMAN 1 Bangko could not be said to be perfect. However, the school has tried to run the Adiwiya program as directed by the Ministry of Environment of the Republic of Indonesia. The Adiwiyata team, which has been formed, has been carried out quite well and has also involved all school members. Activities carried out include planting trees and flowers and recycling waste into valuable items. As for the factors inhibiting the running of the Adiwiyata program at school, apart from the lack of awareness of some students as school residents who are still littering, is flooding caused by natural factors. The Adiwiyata Team has carried out a semisification of road elevation and added drainage channels to prevent flooding